Membaca Masa Depan Generasi Millenial; Analisis Dengan Pendekatan Fenimisme - Muhammad Rizal Fazri (Prodi Sosiologi FISIP Universitas Teuku Umar, 2019)
This paper examines how the millennial generation faces social challenges in the future. This study uses a feminist approach. In the perspective of feminism, there are two terms that describe the activity space for women, namely domestic and public. Domestic space encompasses women's activities related to the household, while public space involves women's activities outside the home, both in interaction with the surrounding community and in the work environment. The challenge for the next millennial generation is equal rights between men and women, in the view of feminism focusing on equal rights, women's participation in work, education, sexual freedom, and reproductive rights. Feminists in the millennial generation today also tend to become